(untitled) (CIPEEX, 2025)
Introduction: Obesity is considered a pandemic disease because it is highly prevalent in developed and developing countries and is associated with respiratory disorders. The waist-to-hip ratio (WHR) is not only an indicator of obesity but is also considered a cardiovascular risk factor. Objective: To relate cardiovascular risk to lung function in industrial workers. Methods: This was a cross-sectional analytical study involving workers in a construction materials industry. The sample consisted of 143 workers. The WHR was calculated by dividing the waist circumference by the hip circumference, and respiratory function was measured by spirometry. Workers were stratified according to WHR (low and high risk). Results: Forty-one (28.7%) of the industrial workers were at high risk, of whom 25 were female. Age was higher in workers with high cardiovascular risk. Peak expiratory flow (PFE) ((∆=0,55 L/s, p<0,001), forced vital ((∆=0,65 L, p<0,001), %CVFpredita ((∆=14%, p<0,001), forced expiratory volume in the first second (VEF1) ((∆=0,55 L, p<0,001), %VEF1predito ((∆=11,18%, p<0,001) were higher in low-risk workers. There was a direct correlation between RCQ and PFE (r=0,26 p<0,001), FVC (r=0.22 p-0.009) and TEF (r= -0.19 p=0.021), while it was inverse for %FEV(1) (predicted) (r=0.35, p<0.001) and the VEF(1) /FVC ratio (r= -0.19, p=0.024). Conclusion: Lung function was better in workers with low cardiovascular risk. However, a direct relationship was observed between WHR and PEF, FVC, and TEF, and an inverse relationship when it came to %FEV(predicted) and the FEV(1) /FVC ratio. For prevention and promotion of cardiorespiratory health, we suggest encouraging weight control, improving dietary quality, and increasing physical activity levels.